Identifikasi Struktur Bawah Permukaan Daerah Potensi Panas Bumi Bajawa dan Sekitarnya Menggunakan Metode Gravitasi - Novianti, Teti Amalia; Perdhana, Radhitya; Zulfian, Zulfian (Universitas Jenderal Soedirman, 2025)
This study aims to identify the subsurface structure of geothermal systems in the Bajawa area, East Nusa Tenggara, using gravity methods based on GGMplus 2013 satellite data. The analysis was conducted on complete Bouguer anomaly data that had been corrected and separated into regional and residual components using Butterworth filters. 3D modeling and 2D cross-section incisions were performed on regional anomalies, having density variations between 1.9 - 3.5 g/cm³, a range of regional anomaly values of 92-138 mGal and depths up to 4.43 km. Based on the results of the analysis of the distribution of rock density values, suspected rock formations as geothermal systems such as the presence of reservoirs from the Nangapanda formation (Np) with densities ranging from 1.9 - 2.66 g/cm³, host rocks from the Aimere Scoria formation (As), Andesite Sasa (Ss), Andesite Inie Lika (Ik), Andesite Mataloko (Mk), Andesite Bobo (Bb) and Andesite Siutoro (Si), Inerie Basalt (Ie), Wabela Basalt (Wa), Lahar Deposit (Lh) and Tuf Welas (Wt) with densities ranging from 2.49 - 2.8 g/cm³ and heat sources from Maumbawa Basalt (Mb) with densities ranging from 2.7 -3.5 g/cm³ and Andesite Wangka (Wn) with densities ranging from 1.9 -2.9 g/cm³. This finding strengthens the indication that the Bajawa area and its surroundings could be a potential prospect area for geothermal systems.